2011
DOI: 10.1007/s10561-011-9255-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of decontamination process of heart valve and artery tissues in European Homograft Bank (EHB): a retrospective study of 1,055 cases

Abstract: To evaluate the efficiency of decontamination practice in European Homograft Bank (EHB), the data of the cardiovascular tissues received during recent 2 years were retrospectively analysed in this study. After initial assessment, the tissues were incubated in a 3-antibiotics' cocktail at 4°C for 20-48 h. The states of contamination were evaluated before and after incubation with the focus on the differences in donor type, tissue type, germ type and incubation time. Amongst 1,055 eligible tissues, 77.2% were he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 13 publications
2
20
0
1
Order By: Relevance
“…This caused a major increase in positivity for all types of strains, including gram-negative and sporogenous bacteriae. Our overall decontamination rate in CVT after the first decontamination is comparable to that of previous reports [14], although our sample was mainly comprised of NHBD. There might be several explanations for the residual percentage of contaminated tissues at the end of the process.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This caused a major increase in positivity for all types of strains, including gram-negative and sporogenous bacteriae. Our overall decontamination rate in CVT after the first decontamination is comparable to that of previous reports [14], although our sample was mainly comprised of NHBD. There might be several explanations for the residual percentage of contaminated tissues at the end of the process.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, Fan et al reported that an AB cocktail of lincomycin, polymyxin B and vancomycin reduced the bacterial contamination rate by 76.8% at 4°C for at least 20h [14]. However, two-step decontamination procedure was effective even at low temperatures in most tissues, including CVT, suggesting that the initial bio-burden was probably very low.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of infection from tissue to recipients has been documented on a number of occasions, despite the fact that infection following the implantation of homografts is rarely reported [4]. To prevent the transmission of microbes to recipients, the microbiological evaluation and decontamination of tissues is commonly practiced in tissue banks around the world [5]. Although special guidelines…”
Section: Discussionmentioning
confidence: 99%
“…2 of the 3 antibiotics of the Tissue Establishments have adopted the less toxic antibiotics and accepted a decrease in the yield of allografts due to insufficient decontamination. Every year, as many as 5-10% of all processed allografts have been discarded for insufficient decontamination in our Tissue Establishment [2]. However, due to the low toxicity of our antibiotics cocktail, the quality of the heart valve and vascular allografts was high and the rate of explantation of these allografts was relatively low [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to low concentrations of different antibiotics during the 20-48 h before cryopreservation reduces the contamination rate to about 5-10% [2,3]. Different Tissue Establishments worldwide, responsible for cardiovascular allograft decontamination, have adopted different cocktails of antibiotics, under different temperature conditions and for varying duration [4][5][6].…”
Section: Introductionmentioning
confidence: 99%